ANALISIS LATIHAN DAN EVALUASI BUKU BAHASA ARAB KURIKULUM 2013 MTS KELAS VIII BERDASARKAN PRESPEKTIF RUSYDHI AHMAD THU’AIMAH - Ajeng Euis Tiandini; Tubagus Kesa Purwasandy; Danang Dwi Basuki (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
This study aims to assess the relevance of exercises and evaluation in the  Bahasa Arab book for the 2013 Curriculum of Grade VIII MTs, based on the perspective of Rusydhi Ahmad Thu’aimah. In this study, the researcher uses qualitative research and a descriptive content analysis method. The data collection technique was carried out through document study, where the researcher reviewed and analyzed the content of the Bahasa Arab book used in Grade VIII MTs to determine whether the elements of exercises and evaluation align with the theory proposed by Rusydhi Ahmad Thu’aimah. The results of the study show that the three elements of exercises and evaluation according to Rusydhi Ahmad Thu’aimah (1989) have been fully met in the Bahasa Arab book for the 2013 Curriculum of Grade VIII MTs. These three elements are language exercises, independent learning, and tests and evaluation. In terms of language exercises, the book provides various activities that focus on language skills, such as exercises in understanding sentence structure, vocabulary usage, and applying Arabic grammar rules in appropriate contexts. These exercises are designed to enhance students’ ability to communicate both orally and in writing. In the element of independent learning, the book provides students with opportunities to learn independently through various activities, such as individual tasks, practice questions, and reflection. The presented material encourages students to actively seek information and practice without fully relying on the teacher’s guidance, thereby fostering greater independence in learning. In the element of tests and evaluation, the book includes assessments that are appropriate to the students’ level of understanding, with formative and summative tests to measure students’ competency achievements. These evaluations are not limited to knowledge alone, but also assess the language skills acquired by students throughout the learning process. Tests are given at the end of each lesson, while evaluations are conducted every three lessons.